JOMEINO 2020
DOI: 10.31039/jomeino.2020.4.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic relationship between stock market returns and macroeconomic variables: An empirical study from Bangladesh

Abstract: In this research paper, attempt has been made to explore the dynamic relationship between stock market and macroeconomic variables i.e. DSE index and three key macroeconomic variables (Exchange rate, Industrial production in and Reserve), by using unit root stationary tests and Johansen co-integration test. Monthly data has been used from June, 2003 to June, 2015 for all the variables, like, DSE index, Exchange rate, Industrial production in and Reserve. Results showed that the variables contained a unit root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Furthermore, India VIX and gold may act as a hedge against crude oil and Nifty respectively. Using Johansen's cointegration, Akter et al (2020) reported that the macroeconomic variables namely the Exchange rate, Index of Industrial production and reserve have significant cointegration with the Dhaka Stock Exchange (DSE). However, they did not find any significant long-run relationship between the chosen macroeconomic variables and the DSE.…”
Section: Literature Review On Macroeconomic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, India VIX and gold may act as a hedge against crude oil and Nifty respectively. Using Johansen's cointegration, Akter et al (2020) reported that the macroeconomic variables namely the Exchange rate, Index of Industrial production and reserve have significant cointegration with the Dhaka Stock Exchange (DSE). However, they did not find any significant long-run relationship between the chosen macroeconomic variables and the DSE.…”
Section: Literature Review On Macroeconomic Variablesmentioning
confidence: 99%
“…However, some of the factors that exist in literature are a mix of the macroeconomic variables and global stock market variables. These are the Foreign Exchange rate (Srivastava, 2010; Akter, Rana, & Anik, 2020); Index of Industrial Production (Srivastava, 2010); Consumer Price Index; Long Term Interest Rates (Srivastava, 2010; Mohammed and Rumman, 2018); Gold (Jain & Biswal, 2016; Bouri, Jain, Biswal, & Roubaud, 2017); Crude oil prices (Basher, Haug, & Sadorsky, 2011), Indian Volatility Index (Shahani & Bansal, 2020) and Morgan Stanley Capital International (MSCI) World Index (Srivastava, 2010; Mensi, Hammoudeh, Yoon, & Balcilar, 2016). In addition to the above mentioned factors, this study considers MSCI emerging market index as a new variable for predicting the Indian stock market in pre and during COVID-19 periods.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the factors that we have identified from the literature are a mix of macroeconomic variables and global stock market variables. These are the Foreign Exchange rate (FX; Srivastava, 2010;Akter et al, 2020); Index of Industrial Production (IIP; Srivastava, 2010;Camilleri et al, 2019); Consumer Price Index (CPI; Megaravalli et al, 2018;Areli Bermudez Delgado et al, 2018); Long Term Interest Rates (LTINT; Srivastava, 2010;Mohammed and Rumman, 2018); Bombay Stock Exchange (BSE) Sensex (Giri and Joshi, 2017;Baranidharan and Dhivya, 2020) and Morgan Stanley Capital International World Index (MSCI; Srivastava, 2010;Mensi et al, 2016). Therefore, to forecast the closing price of the Indian stock market (BSE Sensex), we consider input variables, namely, CPI, LTINT, MSCI World Index, Rupee-Dollar FX and IIP.…”
Section: Dynamic Prediction Of Indian Stock Marketmentioning
confidence: 99%
“…Using Johansen's cointegration, Akter et al (2020) reported that the macroeconomic variables, namely, the exchange rate, IIP and reserve have significant cointegration with the Dhaka Stock Exchange (DSE). However, the results of VECM reveal no significant long-run relationship exists between the chosen macroeconomic variables and the DSE.…”
Section: Literature Review On Macroeconomic Variablesmentioning
confidence: 99%
“…The result showed a weak connection between macroeconomic variables and stock market returns. Akter et al (2020) examine the dynamic relationship between stock market and macroeconomic variables in Bangladesh, using Monthly data from June, 2003 to June, 2015. The DSE index, Exchange rate, Industrial production and Reserve are the study variables.…”
Section: Interest Rate and Stock Market Returnsmentioning
confidence: 99%